Regulatory focus, regulatory fit, and the search and consideration of choice alternatives - PHAM, Michel Tuan (Institutional Knowledge at Singapore Management University, 2010)
This research investigates the effects of regulatory focus on alternative search and consideration set formation in consumer decision making. Results from three experiments yield two primary findings. First, promotion-focused consumers tend to search for alternatives at a more global level, whereas prevention-focused consumers tend to search for alternatives at a more local level. Second, promotionfocused consumers tend to have larger consideration sets than do preventionfocused consumers. Building on these two primary findings, it is additionally shown that whereas promotion-focused consumers attach relatively greater value to options chosen from hierarchically structured sets, prevention-focused consumers attach relatively greater value to options chosen from nonhierarchically structured item lists. Finally, whereas promotion-focused consumers attach significantly greater value to options chosen from larger sets than to options chosen from smaller sets, prevention-focused consumers do not attach significantly less value to options chosen from larger sets than to options chosen from smaller sets.